Insertion Method for Multiple Messenger Problem with Multiple Depots - Jan Fabry (Communications - Scientific letters of the University of Zilina, 2015)
Messenger problem, as the variation of pickup and delivery problem, deals with the transport of a set of packages from their origins to given destinations. In reality, several vehicles have to be used to be able to satisfy all requirements within given time limit. Messengers can be located in one or multiple depots. Because of NP-hardness of the problem it is impossible, for most real problems, to find the optimal solution in acceptable time. Therefore, heuristic algorithms must be used. In the paper, insertion method for routes generation is presented. As the computational experiments in VBA for Excel show, obtained results can be improved using the exchange algorithm.